Circulating Cell-free DNA in Patients With Acute Biliary Pancreatitis: Association With Disease Markers and Prolonged Hospitalization Time—A Prospective Cohort Study. Issue 6 (18th December 2022) - Gibor, Udit; Perry, Zvi; Netz, Uri; Kirshtein, Boris; Mizrahi, Solly; Czeiger, David; Sebbag, Gilbert; Douvdevani, Amos
Abstract : Objective: To evaluate cfDNA as an indicator of pancreatitis severity. Background: Acute pancreatitis severity scores have limited proficiency, and are complex and challenging to use clinically. Elevation of circulating cfDNA concentration has been shown to be associated with hospital length of stay (LOS) and mortality. Methods: In a prospective study, cfDNA concentration was measured by a simple fluorometric test, at admission and for 2 consecutive days, in patients with acute biliary pancreatitis (ABP). Ranson and APACHE II scores were used as measures of pancreatitis severity. Hospital LOS and mortality were used as outcome measures. Results: Seventy-eight patients were included. Patients with severe disease according to Ranson's Criteria (n = 24) had elevated median admission cfDNA compared to patients with mild disease (n = 54, 2252ng/ml vs 1228 ng/ml, P < 0.05 ). Admission cfDNA levels correlated with Ranson and APACHE II scores and markers of bile duct obstruction. LOS did not differ between patients with mild and severe disease according to Ranson and APACHE II scores. Patients with cfDNA at 24 hours concentrations above the cutoff value of healthy patients (>850 ng/ml) had a significantly longer LOS compared to those with normal cfDNA levels ( P < 0.001 ). Conclusions: cfDNA, measured by a rapid simple assay, proved a valuable early marker of severity in ABP with clear advantages for prediction of LOS over Ranson and APACHE II. Measurement of cfDNA has the potential to be an effective practical approach to predict the course of ABP and should be further evaluated in larger trials.